Diagnostic and prognostic significance of serum soluble endoglin levels in preeclampsia and eclampsia - Sachan, Rekha (Adv Biomed Res, 2016)
BACKGROUND: Preeclampsia is a multisystem disorder of unknown etiology that affects 4–5% of all pregnancies. The aim of the study was to evaluate the diagnostic accuracy of serum soluble endoglin (sEng) in preeclampsia and eclampsia and also to evaluate its prognostic significance. MATERIALS AND METHODS: This prospective case–control study carried out over a period of 1 year in the Department of Obstetrics and Gynaecology, King George Medical University, Lucknow. After written informed consent and ethical clearance, total 90 subjects were enrolled. Among them, 30 subjects of eclampsia, 15 of nonsevere preeclampsia, 15 of severe preeclampsia served as cases, and 30 healthy pregnant normotensive women served as controls. Levels were estimated by enzyme-linked immunosorbent assay technique in both cases and controls. RESULTS: Mean level was highest in eclampsia group (14.96 ± 1.96 ng/mL) and lowest in controls (2.08 ± 0.56 ng/mL). At cut-off value of sEng levels of ≥6.26 ng/mL, it was found to be 100% sensitive and 100% specific for the diagnosis of preeclampsia (area under curve =1) at 95% confidence interval. sEng levels were strongly correlated with systolic (r = 0.928) and diastolic blood pressure (r = 0.916), serum lactate dehydrogenase (r = 0.791) and serum uric acid (r = 0.722). All four maternal deaths were reported within eclampsia group, in whom the mean sEng level was significantly higher (17.84 ± 0.22) as compared to other subjects (9.50 ± 5.80). CONCLUSION: sEng is a novel marker for diagnosis of preeclampsia, and it can also be used as a prognostic marker to predict the severity of preeclampsia.